Identifying Ethnomathematics in the Old Mosque of Tosora - Negara Mangkubumi K (SEAMEO Regional Centre for QITEP in Mathematics, 2021)
The superficial understanding and application of cultural values in the life of a pluralistic community is the main reason to conduct this research as a way to introduce the importance of national identity to students through mathematics learning. The provision of real-life problems in this study is expected to enhance the relationship between reality and mathematical knowledge. The old mosque of Tosora in Wajo can be an alternative to introduce mathematical activities based on local wisdom (ethnomathematics). This is qualitative descriptive research using a case study. Data were obtained through interviews, observation, and documentation. Data triangulation was used to check the validity. Furthermore, the data were analysed through Spradley model based on domain analysis and taxonomic analysis. The results showed that the old mosque of Tosora contains some mathematical concepts, mainly geometry. In addition to the philosophy of the building, the four pillars namely panrita (wise and honest), warani (brave), macca (intelligent), and sugi (rich) become the focal principles of Buginese’s life.